Talent development practices and processes in learning organisations: evidence from South African higher education institutions - Abiwu, Lawrence; Martins, Isabel (The learning organization, 2025)
Purpose The purpose of this paper was to identify talent development practices and processes that enhance professional and career growth of employees in South African higher education institutions (HEIs). Design/methodology/approach A quantitative study was carried out to investigate the subject matter. A structured questionnaire was used to collect the data from 265 academics in three South African HEIs. The Statistical Package for the Social Sciences, version 27.0, was used to analyse the data. Cronbach’s alpha coefficient and factor analysis were used to test the reliability and validity of the measuring instrument. Pearson’s correlations and regression analysis were used to interpret the relationship between the independent and dependent variables. Findings The results of the Pearson correlation test established a strong positive influence of training development, coaching and mentoring and career development on talent development. On the other hand, linear regression results indicated that training and development, coaching and mentoring and career development made a strong contribution to the model. Research limitations/implications The scope of the study only applied to South African HEIs, making the generalisation of the findings to be limited because of the differences in an organisational context. Hence, future research should focus on different industries. Practical implications The study contributes to understanding how talent development can be leveraged to assist academics in HEIs to improve their professional and career goals. The findings suggest that HEIs must invest in talent development to help academics acquire the skills, knowledge and competencies required to perform their tasks. Originality/value This paper sheds more light on talent development practices and processes that enhance academic skills, knowledge and competencies in HEIs. Moreover, the study expands on the findings of prior studies concerning talent development in learning organisations.